Systematic Study: Data and Information Management in Management Information Systems in the Digital Era - Andes Prayuda Yunanda; Jhon Veri (SEAN Institute, 2025)
The development of information technology in the digital era has revolutionized the way organizations manage data and information. Management Information Systems (MIS) are a strategic solution for improving the efficiency, accuracy, and security of information management through the integration of modern technologies such as cloud computing, big data analytics, artificial intelligence (AI), and the Internet of Things (IoT). This study uses a Systematic Literature Review (SLR) method on six selected articles to identify the benefits, challenges, and strategies for implementing MIS. The study results show that a well-managed MIS can provide real-time, relevant, and error-free information, thus supporting strategic decision-making. Key obstacles include the digital divide, cybersecurity issues, low digital literacy, and infrastructure limitations. This study recommends a sustainable strategy that includes improving digital literacy, technological updates, data protection policies, and human resource training. With proper management, MIS has the potential to create an adaptive, secure, and highly competitive digital ecosystem.